Identificação e caracterização de marcadores relacionados à agressividade do melanoma - Monteiro, Ana Carolina [UNIFESP] (2019)
Melanoma is the most aggressive, treatment-resistant and metastatic skin cancer. It accounts for 80% of all deaths associated with these malignancies. Importantly, tumor vascularization is a critical step of the metastatic process, which is the main cause of melanoma death. Although tumor metastasis has been intensively studied in the last years, the molecular mechanisms related to it still need to be further elucidated. The murine malignant transformation model established in our laboratory was shown to be a valuable tool to study this lethal disease. Therefore, the aim of this study was to identify and define microRNAs (miRNAs) and genes related to melanoma aggressiveness in this model and to translate it to an clinical application to human patients. Initially, we further characterized the non-metastatic 4C11- cells and the metastatic 4C11+ cells, and certified that 4C11+ cells are highly aggressive in vitro and in vivo. The miRNA profile of 4C11- to 4C11+ cells identified the miR-298 as downregulated in the metastatic 4C11+ cells. In vitro assays with 4C11+ cells overexpressing this miRNA indicate its involvement in the aggressive phenotype. Moreover, this miRNA seems to regulate Angiopoietin 2 (ANGPT2), an important angiogenesis regulator. Expression analysis of cancer-related genes revealed the aggressiveness of 4C11+ cells is strongly associated with the high expression of angiogenic factors, as ANGPT2, Vascular endothelial growth factor C (VEGFC), VEGF receptor-3 (VEGFR-3) and homeobox 1 (SIX1). 5-Aza-CdR-treatment enlightened that the abnormal expression of these genes are epigenetically regulated in the analyzed murine cells. Furthermore, the inhibition of the VEGFC pathway abrogated 4C11+ cells tumorigenic potential in vitro and in vivo, suggesting this pathway has an important tumorigenic activity in these melanoma cells. Finally, TCGA data analysis revealed that ANGPT2 and VEGFR-3 expression, as well as the promotor methylation status of VEGFC, ANGPT2 and SIX1 are independent prognostic factors of overall survival in melanoma patients. The translation of the dysregulated gene expression and methylation status identified in the murine cells to a possible clinical application strongly support the applicability of our melanoma progression model to unravel new biomarkers for this aggressive human disease.